EVALUASI MANAJEMEN PERAWATAN LAMBUNG KAPAL SAAT DOCKING UNTUK MENINGKATKAN EFISIENSI OPERASIONAL KMP BONTANG EXPRESS II: Evaluation of Ship Hull Maintenance Management During Docking to Improve Operational Efficiency of KMP Bontang Express II - Lopo, Elkana Bilak; Pereira Maia Pinto, Gaspar; Adam Tnunay, Imanuel; Hakim, Moh. Lukman; Rosario Nisen Laosana, Okto (PT Yupin Felicitas Utama, 2026)
Sea transportation plays a strategic role in supporting the national logistics system, particularly in archipelagic countries such as Indonesia. The operational reliability of a vessel is strongly influenced by the condition of its hull, which is directly exposed to the corrosive marine environment. This study aims to evaluate hull maintenance management during the docking process in order to improve the operational efficiency of KMP Bontang Express II at PT. Dok dan Perkapalan Surabaya. The research employed a descriptive qualitative approach using a case study method during the docking period from May to July 2024. Data were collected through direct observation, interviews with ship officers and shipyard representatives, and documentation review of maintenance records. Data analysis was conducted using an evaluative approach and root cause analysis, focusing on docking completion timeliness, supervision effectiveness, and the quality of hull maintenance results. The findings indicate that the primary issues were not technical in nature but were related to weak supervision systems, insufficient systematic progress documentation, and suboptimal work schedule coordination. These conditions potentially led to time deviations and the risk of rework. The recommended optimization strategies include the implementation of daily supervision checklists, a structured 24-hour supervisory schedule, routine toolbox meetings, and a stage-based verification system before proceeding to subsequent work phases. This study emphasizes that strengthening a Planned Maintenance System based on active supervision and structured documentation can enhance operational efficiency, reduce long-term corrective costs, and extend the technical service life of the vessel’s hull. The integration of technical control and effective managerial governance is the key to achieving an efficient, economical, and sustainable docking process.